Communal rage in secular India - Zakaria, Rafiq 1920-2005. (Mumbai : Popular Prakashan, 2002)
With reference to Gujarat.
Includes bibliographical references (p. [228]-233) and index.
Keywords: Riots -- India -- Gujarat; Hindus -- India -- Gujarat; Muslims -- India -- Gujarat; Gujarat (India) -- Ethnic relations